Aging Processes in Films of Iron-Yttrium Garnet Implanted by Boron Ions - Yaremiy, I. P.; Povkh, M.M.; Kotsyubynsky, V.O.; Fedoriv, V.D.; Yaremiy, S.I.; Pashkovska, R.I. (Physics and Chemistry of Solid State, 2019)
Based on the results of X-ray structural analysis, changes in the crystalline structure that occurred during 15 years in surface layers of epitaxial films of iron-yttrium garnet implanted by B+ ions were studied. The processes that occur during the B+ ion implantation of in ferrite-garnet films, and the processes that accompany the low-temperature aging of ion-implanted films are considered. Strain profiles were determined from the experimental rocking curves, obtained immediately after ion implantation and after 15 years. It was found that the value of relative maximum deformation of surface layers decreases at constant thickness of the disturbed layer.